FM1-43 is a permeant blocker of mechanosensitive ion channels in sensory neurons and inhibits behavioural responses to mechanical stimuli - Drew Liam J; Wood John N (SAGE Publishing, 2007)
Abstract The molecular identity and pharmacological properties of mechanically gated ion channels in sensory neurons are poorly understood. We show that FM1-43, a styryl dye used to fluorescently label cell membranes, permeates mechanosensitive ion channels in cultured dorsal root ganglion neurons, resulting in blockade of three previously defined subtypes of mechanically activated currents. Blockade and dye uptake is voltage dependent and regulated by external Ca2+. The structurally related larger dye FM3-25 inhibited mechanically activated currents to a lesser degree and did not permeate the channels. In vivo, FMI-43 decreases pain sensitivity in the Randall-Selitto test and increases the withdrawal threshold from von Frey hairs, together suggesting that the channels expressed at the cell body in culture mediate mechanosensation in the intact animal. These data give further insight into the mechanosensitive ion channels expressed by somatosensory neurons and suggest FM dyes are an interesting tool for studying them.